Simulations of the polarisation-dependent Raman intensity of beta-carotene in photosystem II crystals - Brose, K.; Zouni, A.; Mueh, F.; Mroginski, M. A.; Maultzsch, Janina (Chemical Physics, 2013)
In order to clarify possibilities to identify the beta-carotene (beta-Car) radicals in secondary electron transfer (ET) reactions in the photosystem II core complex (PSIIcc), Raman intensities of all 96 beta-Car cofactors in the unit cell of PSIIcc-dimer crystals as a function of polarisation and crystal orientation were simulated based on the 2.9 angstrom resolution structure. The Raman-active symmetry A(g) in the C-2h group is assigned to the beta-Car modes nu(66) and nu(67). Simulations are in agreement with experiment for off-resonant excitation at 1064 nm. Resonant measurements at 476 and 532 nm excitation can not be explained, which is attributed to mode mixing in the excited state and the existence of different spectral pools. The identity of the beta-Car oxidised in secondary ET can not be resolved by Raman measurements on PSIIcc-dimer crystals. Additional simulations show that similar measurements on PSIIcc-monomer crystals could provide a possible route to solve this issue. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Photosystem II; beta-Carotene; Raman spectroscopy; Polarisation dependence; Simulations